Advances in extracorporeal membrane oxygenator design for artificial placenta technology. Issue 3 (4th November 2020) - Blauvelt, David G.; Abada, Emily N.; Oishi, Peter; Roy, Shuvo
Abstract: Extreme prematurity, defined as a gestational age of fewer than 28 weeks, is a significant health problem worldwide. It carries a high burden of mortality and morbidity, in large part due to the immaturity of the lungs at this stage of development. The standard of care for these patients includes support with mechanical ventilation, which exacerbates lung pathology. Extracorporeal life support (ECLS), also called artificial placenta technology when applied to extremely preterm (EPT) infants, offers an intriguing solution. ECLS involves providing gas exchange via an extracorporeal device, thereby doing the work of the lungs and allowing them to develop without being subjected to injurious mechanical ventilation. While ECLS has been successfully used in respiratory failure in full‐term neonates, children, and adults, it has not been applied effectively to the EPT patient population. In this review, we discuss the unique aspects of EPT infants and the challenges of applying ECLS to these patients. In addition, we review recent progress in artificial placenta technology development. We then offer analysis on design considerations for successful engineering of a membrane oxygenator for an artificial placenta circuit. Finally, we examine next‐generation oxygenators that might advance the development of artificial placenta devices.